Un rapporto di Ferigo Foscari, Bailo veneto a Costantinopoli nel 1795: “l’Arsenale dei Dardanelli” - İşler, Didem (Oriente moderno, 2020)
Abstract The report of Bailo Ferigo Foscari dated April 10, 1795, protect in the Venetian State Archive today, includes an unpublished architectural drawing about the renovation of Gallipoli Shipyard that with its strategic location and production capacity one of the most important naval bases of the Ottoman Empire. The drawing, which is among the “Senato Dispacci Costantinopoli” documents that not only provides contributions to the history studies by shedding light on the political and military developments of the periods in terms of Venetian-Ottoman relations in archival studies, but also is an extremely valuable evidence that contributes to the art and architectural history as a visually documenting the Gallipoli shipyard, which has not survived to the present day.